In-Hospital Mortality of Patients with ST Elevation Myocardial Infarction in Diabetic Versus Non-Diabetic Patients - Nouman Khan, Muhammad Shafique Arshad, Abat Khan, Muhammad Omer Hashmi, Nabil Younas, Taskin Ahmad Khan Rathore, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Diabetic mellitus is an epidemic health issue causing almost twice the mortality compared to non-diabetic. Diabetes and non-diabetics with acute myocardial infarction were compared for in-hospital mortality and complications. Material and Methods: This comparative cross-sectional study was conducted on 264 successive diabetic and non-diabetic patients in the Department of Cardiology Pakistan Institute of Medical Sciences Islamabad with study duration of 6 months. All the acute myocardial infarction patients with ST-elevation were admitted and treated with thrombolytic agent such as streptokinase. Patients were categorized into two groups: 1) Diabetic patients 2). Non-diabetic patients. All the patients of either gender with age ranges from 15 years to 80 years and having chest pain for >30 minutes and <24 hours with ST-elevation were enrolled. After 60 minutes of thrombolysis, an ECG was taken to measure the baseline and the following day's ECG. SPSS version 26 was used for data analysis. Results: Out of 264 patients, there were 196 (74.2%) male and 68 (25.8%) females. Diabetic and non-diabetic group included 132 patients. Diabetic group patients had higher frequency of ST elevation in myocardial infarction than non-diabetic patients. Brady arrhythmias, post MI angina, LV failure, atrial fibrillation, and cardiogenic shock were the main complications observed in all the patients after ST Elevation MI. Diabetes patients are more likely to experience all these complications post MI angina than non-diabetics. Conclusion: The present study concluded that the prevalence of arrhythmias and left ventricular failure complications were higher in diabetic patients. Also, the mortality rate was significantly higher in diabetic patients. The non-diabetic patients had higher post MI angina than diabetic patients. It is also important to decrease the prevalence of diabetes mellitus in our population since it is a modifiable risk factor that leads to more complications following MI than non-diabetic patients. Keywords: In-hospital mortality, ST elevation, Myocardial infarction, diabetic and non-diabetic